Karakteristik Campuran Asbuton pada Lapis Aus AC-WC ada Lapis Aus AC-WC dengan Penambahan BGA B 5/20 sebagai Agregat Halus pada Aspal Pengikat 60/70 - Kurnia, Andreni Octora; Firdaus, Firdaus; Febriansyah, Dinar (Jurnal Talenta Sipil, 2025)
Premature pavement damage caused by heavy traffic loads remains a major challenge in Indonesia’s transportation infrastructure. One potential solution is the use of local materials such as Asbuton, particularly Buton Granular Asphalt (BGA) type B 5/20, as fine aggregate. This study aims to analyze the Marshall characteristics of Asphalt Concrete–Wearing Course (AC-WC) mixtures incorporating BGA B 5/20 and fly ash as filler. The research employed the Marshall test method on 60 specimens, with variations in asphalt content (5%–7%) and BGA composition (2%, 2.5%, and 3%) combined with 1.5% fly ash. Parameters evaluated include stability, flow, density, and Marshall Quotient (MQ). The results show that the optimum asphalt content of 6.2% provided the best performance in the mixture containing 2% BGA and 1.5% fly ash, yielding a stability of 1,755.21 kg, flow of 3.21 mm, density of 2.271 gr/cc, and residual MQ of 98.18%. All values met the Indonesian Ministry of Public Works specifications for heavy traffic pavements. In conclusion, the incorporation of BGA B 5/20 enhances the stability and deformation resistance of AC-WC mixtures, supporting the sustainable use of local materials in road construction.